2008
DOI: 10.1080/00223890802248919
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Beck Depression Inventory–II in Low-Income, African American Suicide Attempters

Abstract: Cross-cultural examinations of the validity and reliability of the Beck Depression Inventory-II (Beck, Steer, Ball, & Ranieri, 1996) is essential for its use in assessment and monitoring of the effectiveness of suicide interventions across racial groups. We tested the fit of a second-order, two-factor model and the internal reliability of the BDI-II in a sample of 133 African Americans with a recent history of suicide attempts. Additionally, we examined the convergent validity with the Hamilton Rating Scale fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 13 publications
3
49
0
1
Order By: Relevance
“…Scores of 20 to 28 indicate moderate depression, and scores of 29 to 63 indicate severe depression . High internal consistency with coefficient alphas of .90 and above has been demonstrated among psychiatric outpatients (Beck, Steer, Ball, & Ranieri, 1996) and recent suicide attempters (Joe, Woolley, Brown, Ghahramanlou-Holloway, & Beck, 2008). The present study found comparable internal consistency (a ¼ .90).…”
Section: Assessment Of Depression and Suicidalitysupporting
confidence: 80%
“…Scores of 20 to 28 indicate moderate depression, and scores of 29 to 63 indicate severe depression . High internal consistency with coefficient alphas of .90 and above has been demonstrated among psychiatric outpatients (Beck, Steer, Ball, & Ranieri, 1996) and recent suicide attempters (Joe, Woolley, Brown, Ghahramanlou-Holloway, & Beck, 2008). The present study found comparable internal consistency (a ¼ .90).…”
Section: Assessment Of Depression and Suicidalitysupporting
confidence: 80%
“…Por otra parte, si bien el BDI-II se presenta como una versión más actualizada del BDI-IA, la cual integra nueve, en vez de siete, de los síntomas enlistados como criterios diagnósticos en el DSM-IV (APA, 1995) para la depresión, y amplía su tiempo de evaluación a las dos últimas semanas, su composición factorial y propiedades psicométricas no difieren en gran medida de las informadas para el BDI-IA (Joe, Woolley, Brown, Ghahramanlou-Holloway & Beck, 2008), cargando también para un factor somático y un factor cognitivo-afectivo, en adolescentes y adultos.…”
Section: Discussionunclassified
“…Adolescent depression occurs within various developmental, social, economic, and cultural contexts, which is often manifested by known depressive symptoms of fatigue, loss of interest in daily activities, sad moods, and sleep disturbances. It has also been noted that acts of anger, frustration, and violence among minority adolescents, often categorized as behavioral problems, have also been linked with depression, especially among males (Fitzpatrick, Dulin, & Piko, 2010;Joe, Woolley, Brown, Ghahramanlou-Holloway, & Beck, 2008;Rosenbloom & Way, 2004). Reports on adolescent depression suggest a general trend of higher rates of depression among minority adolescents and conclude that minority adolescents are a high-risk group for poor mental health outcomes (Eaton et al, 2008;U.S.…”
Section: Introductionmentioning
confidence: 94%